Dukungan Keluarga Dalam Merawat Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialisa - Ade Tika Herawati (NHM PRESS, 2021)
Background: According to Kidney Disease Statistics in (2017) the main causes of chronic kidney disease are diabetes 44%, high blood pressure 28%, Glomerulonephritis 6.3%, congenital disease 2.2%, urogenital disease 1.3%, and others by 18.4%. Factors that affect the quality of life of CKD patients undergoing hemodialysis include age, physical, psychological, social, environmental, economic and family support factors. Family support is a process of relationship between the family and its social environment that can be accessed by the family that can be supportive and provide assistance to family members. Research method: this is a descriptive research method. The population in this study was 55 patients undergoing hemodialysis therapy at RSUD Kota Bandng 2021. and the sample used in this study was purposive sampling with a total of 36 respondents. The instrument used was a family support questionnaire. The analysis used univariate analysis to describe descriptive family support. The results of the study: it was found that most of the family support in this study was in the very supportive category (54.3%), the assessment support in this study was mostly in the supportive category (57.1%). Almost half of Instrumental Support in this study is categorized as Support (42.9%). Most of the information support in this study is categorized as very supportive (54.3%). Most of the Emotional Support in this study was categorized as very supportive (57.1%). Conclusion: The data from the research and discussion can be concluded that the description of family support in treating chronic CKD patients undergoing hemodialysis therapy is generally categorized as supportive family support. Recomendation : Families are more supportive to families who are undergoing hemodialysis therapy.